Entre morros e olhares: a percepção ambiental de moradores frente aos riscos de deslizamentos em bairros de Caxias/MA (Terr@ Plural, 2020)
Investigations about the relationship between society and nature are considered important elements for understanding several scenarios of ownership, belonging, and processes associated to the existence of risks and vulnerabilities. This paper aims to understand the environmental perception of residents of Cangalheiro and Vila Alecrim districts, in the city of Caxias (MA), about the risks and vulnerabilities related to landslides. The methodology was supported by theoretical analysis, conducting interviews, field activities, and geoprocessing. It was found that although the majority of participants stating that they do live in risk areas and that they have been targets of some topographical disaster-related, many point out that they do not consider to change address once there are their affective and belonging memories